Tren publikasi collaborative governance sebuah analisis bibliometrik - Ladiatno Samsara (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction: This study aims to analyze publication trends related to collaborative governance indexed in Scopus database from first year of publication until June 2022. Data Collection Methods: Collaboratove Governance field journal articles published between 1977-2022 were searched from the scopus database using